Rhinovirus Infections and Associated Respiratory Morbidity in Infants: A Prospective Cohort Study. Issue 10 (October 2016) - Mack, Ines; Kieninger, Elisabeth; Cangiano, Giulia; Tapparel, Caroline; Kuehni, Claudia; Spycher, Ben; Kaiser, Laurent; Frey, Urs; Regamey, Nicolas; Latzin, Philipp
Abstract : Background: Risk factors promoting rhinovirus (RV) infections are inadequately described in healthy populations, especially infants. Objectives: To determine the frequency of symptomatic and asymptomatic RV infections and identify possible risk factors from host and environment among otherwise healthy infants. Methods: In a prospective birth cohort, respiratory health was assessed in 41 term-born infants by weekly telephonic interviews during the first year of life, and weekly nasal swabs were collected to determine RV prevalence. In a multilevel logistic regression model, associations between prevalence and respiratory symptoms during RV infections and host/environmental factors were determined. Results: Twenty-seven percent of nasal swabs in 41 infants tested positive for RVs. Risk factors for RV prevalence were autumn months [odds ratio (OR) = 1.71, P = 0.01, 95% confidence interval (CI): 1.13–2.61], outdoor temperatures between 5 and 10°C (OR = 2.33, P = 0.001, 95% CI: 1.41–3.86), older siblings (OR = 2.60, P = 0.001, 95% CI: 1.50–4.51) and childcare attendance (OR = 1.53, P = 0.07, 95% CI: 0.96–2.44). Fifty-one percent of RV-positive samples were asymptomatic. Respiratory symptoms during RV infections were less likely during the first 3 months of life (OR = 0.34, P = 0.003, 95% CI: 0.17–0.69) and in infants with atopic mothers (OR = 0.44, P = 0.008, 95% CI: 0.24–0.80). Increased tidal volume (OR = 1.67, P = 0.03, 95% CI: 1.04–2.68) and outdoor temperatures between 2 and 5°C (OR = 2.79, P = 0.02, 95% CI: 1.17–6.61) were associated with more symptoms. Conclusions: RVs are highly prevalent during the first year of life, and most infections are asymptomatic. Frequency of RV infections is associated with environmental factors, while respiratory symptoms during RV infections are linked to host determinants like infant age, maternal atopy or premorbid lung function. Abstract : Supplemental Digital Content is available in the text.